2020
DOI: 10.1128/msystems.00268-20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glyphosate on the Honey Bee Gut Microbiota: Effects of Intensity, Duration, and Timing of Exposure

Abstract: Exposure to anthropogenic chemicals may indirectly compromise animal health by perturbing the gut microbiota. For example, the widely used herbicide glyphosate can affect the microbiota of honey bees, reducing the abundance of beneficial bacterial species that contribute to immune regulation and pathogen resistance. Previous studies have not addressed how this impact depends on concentration, duration of exposure, or stage of microbiota establishment. Worker bees acquire their microbiota from nestmates early i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 56 publications
4
62
1
Order By: Relevance
“…Unfortunately, this precludes any comparisons between the glyphosate concentrations detected in our experiments with concentrations detected in honey in other studies (44)(45)(46)(47), but it does show that bees can directly transfer contaminated resources to hive compartments. A recent study using bees under laboratory conditions showed that glyphosate has a persistent impact on the gut microbiota of young adult workers whether exposure occurs during or after microbiota establishment and that this impact is dose dependent (88).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this precludes any comparisons between the glyphosate concentrations detected in our experiments with concentrations detected in honey in other studies (44)(45)(46)(47), but it does show that bees can directly transfer contaminated resources to hive compartments. A recent study using bees under laboratory conditions showed that glyphosate has a persistent impact on the gut microbiota of young adult workers whether exposure occurs during or after microbiota establishment and that this impact is dose dependent (88).…”
Section: Discussionmentioning
confidence: 99%
“…The glyphosate mechanism of action is through inhibition of the growth of weeds by interfering with the production of essential aromatic amino acids by inhibiting EPSPS, which is responsible for chorismate biosynthesis, an intermediate in the biosynthesis of phenylalanine, tyrosine and tryptophan (7). Then, from the moment glyphosate inhibits it, these bacteria are unable to maintain normal levels in the gut microbiome (111,(113)(114)(115). Thus, new studies evaluating the involvement of the gut-thyroid axis are relevant in advancing the knowledge of glyphosate toxicity on thyroid function.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This is corroborated by studies where gut microbiota dysbiosis was correlated to Hashimoto’s thyroiditis ( 102 104 ), Graves’ disease ( 104 ), thyroid cancer and thyroid nodules ( 105 ). In parallel in the field of toxicology, recent studies indicate that GBH is able to affect the intestinal microbiome of mice ( 106 ), rats ( 107 – 112 ), honeybees ( 113 , 114 ), Japanese quails ( 115 ) and Daphnia magna ( 116 ). A possible explanation for this toxicity is that some classes of bacteria require the shikimate pathway (5-enolpyruvylshikimate-3-phosphate synthase, EPSPS) for their metabolism.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recent studies have shown that glyphosate alters the structure and composition of the honey bee gut microbiota through the inhibition of the EPSPS enzyme, which can be coded by the genome of several microorganisms [ 15 , 16 , 17 , 18 ]. The gut microbiota plays an important role in honey bee metabolism, growth, development, immunity and defense against pathogens [ 19 , 20 ], so alterations of this community (dysbiosis) could have severe consequences on honey bee health.…”
Section: Introductionmentioning
confidence: 99%